Does academic culture influence student satisfaction? State of the Covid-19 pandemic period - Pratomo, Saifurrahman Iman; Hendrayati, Heny; Dirgantari, Puspo Dewi; Furqon, Chairul; Wahyudi, Yudi; Sriyono, Sriyono (Jurnal Penelitian Pendidikan, 2023)
The Automotive Engineering Education Study Program (PTO) at the Faculty of Technology and Vocational Education (FPTK), Universitas Pendidikan Indonesia (UPI), is a recently established program that is currently confronted with the challenges posed by the Covid-19 pandemic. Despite these circumstances, it is imperative for the study program to persist in delivering its academic offerings. The influence of the pandemic on academic culture has the potential to affect student satisfaction and the quality of services offered. The objective of this study was to assess the impact of service quality and academic culture on student satisfaction within the study program at PTO FPTK UPI during the COVID-19 pandemic. Descriptive and explanatory surveys are the methodologies employed in this study. The study sample consisted of 32 students enrolled in the PTO study program from the 2019-2021 cohort. The present study incorporates service quality and academic culture as exogenous variables, with student satisfaction being considered as an endogenous factor. The data analysis employed the technique of multiple linear regression, which was conducted using the software programs SPSS 23 and Microsoft Excel. The study's conclusions indicate that while there is no discernible impact on academic culture, there is a substantial relationship between service quality and satisfaction among students. Simultaneously, these two factors exert a significant influence on student satisfaction.
Keywords: academic culture; service quality; student satisfaction